Digestão anaeróbia de um polímero à base de fécula de mandioca - Cremonez, Paulo André (2019)
ABSTRACT: Researchers have focused on biodegradable plastics production to reduce environmental impacts due to the increasing development of the food industry and packaging residues production. Despite the great advantage on using these biodegradable compounds, few researches aim at determining the degradation of these materials under different releasing conditions based on organic waste treatment processes. Thus, this trial was divided into 3 chapters, and aimed at testing anaerobic biodigestion process of biodegradable polymers based on manioc starch to determine its potential for degradation and biogas production, by varying organic loads that are under this process. In Chapter 1, a review concerning the state of art was developed, whose main topics are related to the process of digestion and biopolymers. In Chapter 2, the reasons of inoculum/substrate 0,04, 0,08, 0,2, 0,6 e 1 (gVS/gVS) were tested, using batch reactors (3.2 liters of usable volume), under 37 °C, with 3 replications. In addition, there were 5 destructive samples for each treatment. It was defined that HRT was of 32 days. The results obtained by the regression curves showed that the smaller inoculum/substrate ratio is the best to remove organic matter (above 90%) and biogas production (1027 mL biogas/gVSadd). Besides, some predominance of acidogenic phase with high hydrogen production was observed in the beginning of digestion, while bacteria producers of methane prevailed after the 13th digestion day. Thus, in Chapter 3, the goal was to carry out the anaerobic digestion process and separate acidogenic and methanogenic phases physically. A 3.8-liter useful volume reactor was used with a stirring system coupled to the acidogenic phase, and a 10-liter reactor with a useful volume for methanogenic phase, both operated in a mesophilic temperature range. The Acidogenic reactor was submitted to polymer loads of 8 g/L, 10 g/L, 12 g/L e 14 g/L (humid base), and its effluent was taken to the Methanogenic reactor. The HRTs were defined in 5 and 20 days for the acidogenic and methanogenic reactors, respectively. Based on the obtained results, it was observed that one of the best results was registered with a 10-g/L concentration to produce hydrogen (19.93 mL/gVSadd) and methane (249.13 mL/gVSadd), in the respective phases. This treatment also showed the highest concentrations of gases in biogas (43.17% for hydrogen in Phase 1 and 76.62% for methane in Phase 2), and 84.04% of solids removal at the end of the methanogenic phase. So, it can be concluded that the studied polymer has a high potential for degradation by anaerobic digestion route, which produced biogas with high energy power, rich in methane and hydrogen. Despite this, even considering the separation of acid and methanogenic phases, very high loads of polymer can cause disturbances and collapse in digestion system by the high production of volatile acids.